Eastward salinity anomaly propagation in the intermediate layer of the North Pacific. Issue 2 (25th February 2017) - Kouketsu, Shinya; Osafune, Satoshi; Kumamoto, Yuichiro; Uchida, Hiroshi
Abstract: An objective mapping with the data of profiling float array, maintained under the Argo project, revealed eastward propagation of long‐term (>5 years) salinity anomalies in the subsurface and deep neutral density (γ) layers of 27.0–27.6γ along the subarctic front in the North Pacific after 2000. Such propagation was previously inferred from water property variations along a few observation lines and from numerical simulations, mainly for shallow layers. In the western North Pacific, the signs of the anomalies were the same on and below the 27.0γ, whereas in the eastern North Pacific the sign on 27.0γ was opposite to those on 27.4γ. This difference was attributed mainly to slower advection in the deeper layers. These changes were larger than the standard errors inferred from the objective mapping at least. Furthermore, the variation revealed by the float array was similar to decadal changes observed along repeat ship‐based observation lines, and they were also associated with changes in apparent oxygen utilization especially along 165°E. The small salinity changes in the deeper layers inferred from the float array were also detected as decadal differences in highly accurate trans‐basin observations. Furthermore, because the extension of small changes into the subtropical gyre was also captured by the float and ship‐based observations, the influence of the decadal changes on the isopycnal surfaces off the coast of Japan could appear relatively quickly, even in deeper layers (27.0–27.4γ) in the North Pacific. Key Points: A profiling float array revealed broad propagation of salinity anomalies on the isopycnal surface below 27.0 kg m –3 in the North Pacific The spatial pattern formed by the anomaly propagation was similar to those detected by repeat and highly accurate ship‐based observations The anomaly propagation was consistent with geostrophic advection and might be a part of the bidecadal changes reported in previous studies